Concern, Custom and Common Sense - Kazen, Thomas (Journal for the study of the historical Jesus, 2015)
This essay interacts with E.P. Sanders’s work on purity, building on some of his insights, while disagreeing on other points. Sanders’s appeal to historical imagination and common sense is discussed and problematized. The essay deals at length with issues such as the expulsion, isolation, and integration of various impurity bearers, and the emergence of additional water rites to mitigate impurities and prevent unnecessary contamination. The evidence under discussion includes Hebrew Bible, Dead Sea texts, Philo, Josephus, New Testament, and rabbinic literature.